2018
DOI: 10.3332/ecancer.2018.797
|View full text |Cite
|
Sign up to set email alerts
|

Natural history of castration-resistant prostate cancer in sub-Saharan African black men: a single-centre study of Nigerian men

Abstract: PurposeNative sub-Saharan African black men (SSBM) are disproportionately impacted by higher stage and incurable forms of prostate cancer (PCa). This study evaluates the natural history and survival of a cohort of SSBM with castration-resistant prostate cancer (CRPC).MethodsA retrospective study of patients with CRPC as defined by the Prostate Cancer Working Group 2 managed at a centre in sub-Saharan Africa between January 2011 and December 2015 was conducted. The principal endpoint was overall survival (OS). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…We report a high magnitude of CRPC with half of patients treated for advanced PC by androgen deprivation developing CRPC. This is similar to what others have reported [12]. It is important to identify patients with CRPC since there are targeted therapeutics which can improve both survival and quality of life [17][18].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…We report a high magnitude of CRPC with half of patients treated for advanced PC by androgen deprivation developing CRPC. This is similar to what others have reported [12]. It is important to identify patients with CRPC since there are targeted therapeutics which can improve both survival and quality of life [17][18].…”
Section: Discussionsupporting
confidence: 89%
“…Prostate cancer including CRPC is still a dilemma in low income countries given the morbidity and the cost needed to manage such patients [12]. Patients in sub-Saharan Africa have been shown to have poor access to active treatment of their CRPC [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This state is referred to as castration-resistant prostate cancer (CRPC), and it is characterized by loss of ability to respond to androgen deprivation therapy and the recurrence of prostate cancer and subsequent metastasis (7). This recurrence of disease may occur in up to 40% of the patients (8, 9). For example, Bello (9) reported that 48 of 161 prostate cancer patients in Sub-Saharan Africa treated with androgen deprivation therapy developed CRPC, over a period of 4 years.…”
Section: Introductionmentioning
confidence: 99%
“…This recurrence of disease may occur in up to 40% of the patients (8, 9). For example, Bello (9) reported that 48 of 161 prostate cancer patients in Sub-Saharan Africa treated with androgen deprivation therapy developed CRPC, over a period of 4 years. Hence, CRPC continues to make prostate cancer the leading source of cancer mortality for men, particularly among the black race (4).…”
Section: Introductionmentioning
confidence: 99%